Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1128/jb.179.7.2373-2381.1997
|View full text |Cite
|
Sign up to set email alerts
|

Generation of buds, swellings, and branches instead of filaments after blocking the cell cycle of Rhizobium meliloti

Abstract: Inhibition of cell division in rod-shaped bacteria such as Escherichia coli and Bacillus subtilis results in elongation into long filaments many times the length of dividing cells. As a first step in characterizing the Rhizobium meliloti cell division machinery, we tested whether R. meliloti cells could also form long filaments after cell division was blocked. Unexpectedly, DNA-damaging agents, such as mitomycin C and nalidixic acid, caused only limited elongation. Instead, mitomycin C in particular induced a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
66
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 36 publications
8
66
0
Order By: Relevance
“…Our results concerning the expression of ftsZ Cg under Plac are in partial agreement with the results obtained in Rhizobium (Sinorhizobium) meliloti (another rod-shaped bacterium that lacks MreB homologues) (Latch & Margolin, 1997) and Mycobacterium tuberculosis (Dziadek et al, 2002). It may be concluded that in rod-shaped micro-organisms lacking MreB, branching and swelling are default pathways for increasing mass when cell division is blocked either by FtsZ overproduction (Latch & Margolin, 1997) or by partial depletion of FtsZ (this work).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our results concerning the expression of ftsZ Cg under Plac are in partial agreement with the results obtained in Rhizobium (Sinorhizobium) meliloti (another rod-shaped bacterium that lacks MreB homologues) (Latch & Margolin, 1997) and Mycobacterium tuberculosis (Dziadek et al, 2002). It may be concluded that in rod-shaped micro-organisms lacking MreB, branching and swelling are default pathways for increasing mass when cell division is blocked either by FtsZ overproduction (Latch & Margolin, 1997) or by partial depletion of FtsZ (this work).…”
Section: Discussionsupporting
confidence: 81%
“…It may be concluded that in rod-shaped micro-organisms lacking MreB, branching and swelling are default pathways for increasing mass when cell division is blocked either by FtsZ overproduction (Latch & Margolin, 1997) or by partial depletion of FtsZ (this work). Daniel & Errington (2003) used fluorescent vancomycin to determine the spatial pattern of peptidoglycan biosynthesis in C. glutamicum, and observed that cell division septa and cell poles were labelled by vancomycin.…”
Section: Discussionmentioning
confidence: 99%
“…In E. coli, a low level overproduction of FtsZ causes minicell formation and higher levels inhibit cell division (Ward and Lutkenhaus 1985). In Rhizobium meliloti, overproduction of either of the two FtsZ proteins causes branching and swelling of cells (Latch and Margolin 1997). There is a similar requirement for control of the level of at least one other cell division protein.…”
Section: Discussionmentioning
confidence: 79%
“…We cannot deduce the molecular mechanism underlying this phenotype; however, the morphological changes resulting from the plasmid-mediated expression of S. meliloti DnaA are very similar to the pleomorphic cell shape phenotype reported for S. meliloti cells overexpressing FtsZ or when treated with DNA-damaging agents (Latch & Margolin, 1997). It would seem that the default pathway for a block in cell division that arises from perturbations in chromosome replication in this endosymbiont is a complex change in cell shape.…”
Section: Dnaa Binds To Predicted Binding Sites In the Heme-y02793 Intmentioning
confidence: 79%